Potensi Sistem Integrasi Ternak-Tanaman Pangan dan Hortikultura sebagai Agroeduwisata Berkelanjutan : Kajian Ontologis, Epistemologis, dan Aksiologis di Irigasi Batu Bulan, Sumbawa - Amrullah Amrullah; Muhammad Sarjan; Ahmadi Ahmadi; Sudarli Sudarli; Gunawan Gunawan; Asrul Hamdani; Edy Wahyu Satria (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The integration of livestock-food crops and horticulture is a strategic approach in realizing a sustainable agricultural system, especially in irrigated areas such as the Batu Bulan irrigation in Sumbawa Regency. This system not only increases resource efficiency through the utilization of crop waste as animal feed, the use of organic fertilizer from feces, and the planting of legumes to improve soil fertility, but also has the potential to be developed into agro-edutourism that can increase farmers' income. This study aims to analyze the potential of integration from the perspective of ontology, epistemology, and axiology, and assess its relevance as a basis for developing sustainable agro-edutourism. The method used is a systematic narrative review of international literature (2015-2024) covering the themes of agriculture-livestock integration, agro-edutourism, sustainability, and the philosophy of science. The results of the study indicate that livestock-crop integration has an ontological basis as an integrated agroecological system, an epistemological basis through scientific and local knowledge, and an axiological basis as a source of economic, educational, and ecological value. The development of integrated agro-educational tourism in the Batu Bulan irrigation system has the potential to increase farmer incomes, improve soil health, and strengthen local food security. With institutional support, technology, and multi-stakeholder collaboration, this model can become a viable and valuable strategy for sustainable agricultural development.